TRANSFORMASI KETERAMPILAN PEMASARAN MELALUI PENDAMPINGAN DIGITAL MARKETING BAGI PELAKU KUBE DI DESA KUALA SEMPANG KECAMATAN SERI KUALA LOBAM KABUPATEN BINTAN - Tubel Agusven; Selvi Fauzar; Muhammad Rizki; Agustinus Sihombing; Muqtafin, Muqtafin; Nanda Kristia Santoso (Bajang Institute, 2025)
Kuala Sempang Village, located in Bintan Regency, is known for its local products, such as snacks and chips made from agricultural and plantation produce. However, the limited knowledge and skills in digital marketing pose a significant challenge for members of the Joint Business Group (Kelompok Usaha Bersama, KUBE) in developing their businesses. To address this issue, the Community Service Program (KKN) Group 2 in Kuala Sempang Village conducted digital marketing mentoring aimed at training KUBE members to understand and apply digital-based marketing strategies. The benefits of this activity include enhancing KUBE members' understanding of using social media and digital marketing, which is expected to improve product competitiveness and expand market reach. Evaluation results indicate that participants successfully grasped the fundamentals of digital marketing, although some still require further strengthening in specific aspects. It is recommended that the village government continue to provide support and access to digital technology to ensure the sustainable growth of these businesses. In conclusion, this mentoring initiative has positively contributed to local economic development through digital transformation